2001
DOI: 10.1103/physrevlett.87.223001
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Pseudospin Resonance

Abstract: A new type of resonance is discovered in Rydberg atoms placed in a constant magnetic field -->B and a transient electric field that rotates at the constant frequency -->omega in a plane perpendicular to -->B. The dynamics is explained in terms of two pseudoparticles with spin 1 / 2 in two generalized magnetic fields. The resonance frequency is predicted and found at -->omega = (e/2m)-->B, where -e/m is the electron's charge-to-(reduced)mass ratio. We discuss the applicability of the resonance to accurate magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…This description is very attractive due to its simplicity and accuracy. It was used recently in analysis of state control by external fields [28], experimental data on microwave ionization resonances [26], adiabatic or near-adiabatic state transformations [29][30][31][32], and intrashell single-photon resonances for circularly polarized fields [33]. It is used here to derive analytical expressions for positions and widths of intrashell multiphoton resonances.…”
mentioning
confidence: 99%
“…This description is very attractive due to its simplicity and accuracy. It was used recently in analysis of state control by external fields [28], experimental data on microwave ionization resonances [26], adiabatic or near-adiabatic state transformations [29][30][31][32], and intrashell single-photon resonances for circularly polarized fields [33]. It is used here to derive analytical expressions for positions and widths of intrashell multiphoton resonances.…”
mentioning
confidence: 99%
“…In yet another previous study it was shown that circular Rydberg states in a homogeneous magnetic field show resonance behaviour when perturbed by a harmonic electric field [6]. The resonances may shift and broaden when the strength of the harmonic field is increased [8].…”
Section: Introductionmentioning
confidence: 91%
“…This was predicted only recently on theoretical grounds [3]. Since then, the reduction has been tested in just a few cases [4][5][6][7][8]. Due to the prominence of the Coulomb potential and the importance of symmetry in general, the region of applicability of the two-state reduction scheme should be tested thoroughly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of CESs in external fields was described in [2,3,8]. Intrashell dynamics of the Stark-Zeeman split n = 25 shell in Li was studied extensively over the last 10 years [9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%